Euro-par 2010 parallel processing workshops HeteroPar, HPCC, HiBB, CoreGrid, UCHPC, HPCF, PROPER, CCPI, VHPC, Ischia, Italy, August 31-September 3, 2010, revised selected papers - Guarracino, Mario R.; Vivien, Frédéric; Traff,Jesper Larsson; Cannatoro, Mario; Danelutto, Marco; Hast, Anders; Perla, Francesca; Knupfer, Andreas; Di Martino, Beniamino; Alexander, Michael (Lecture notes in computer science, 2011)
This book constitutes thoroughly refereed post-conference proceedings of the workshops of the 16th International Conference on Parallel Computing, Euro-Par 2010, held in Ischia, Italy, in August/September 2010. The papers of these 9 workshops HeteroPar, HPCC, HiBB, CoreGrid, UCHPC, HPCF, PROPER, CCPI, and VHPC focus on promotion and advancement of all aspects of parallel and distributed computing.